Implementation of Reward and Punishment in Forming Discipline Charachter Early Childhood - Tri Yuningsih, Titin; Sunaryo, Ilham (Early Childhood Research Journal (ECRJ), 2021)
According to the theory of Sr. Bondreward and punishment functions to influence positive responses or negative responses. The purpose of a positive response is to change someone's behavior for the better so that their good behavior will always repeat or increase. Meanwhile, the purpose of negative responses is to eliminate someone's bad behavior. Discipline is generally understood as personality and proper rules with certainty or personality that is gained from training such as, for example, "discipline in the classroom" (Dr. Thomas Gordon, 1996: 3). This study aims to analyze a literature, scientific articles, journals and documents. This study has the results to determine the application of reward and punishment when building characteristicsearly childhood discipline. In tracing research articles carried out in several databases using a word and the concept of special privileges in the 2016-2020 period. From several searches, it was found that 100 national and international research journals, 65 journals met the criteria, 35 journals did not meet the criteria and 20 journals met the criteria consisting of 15 national journals and 5 international journals. Literature review shows that the application of reward and punishments when building characteristicsearly childhood discipline Early stages have variations in several aspects of research design, sample and population (individuals involved), variables, methods, data analysis, specificity, and effectiveness. From statistical data analysis, it shows that a method used can increase the knowledge and actions of parents. Application of reward and punishments when building characteristicsearly childhood disciplinecan form discipline and change attitudes or behavior of children for the better.